Incentives and Institutional Reform in Tax Enforcement: An Analysis of Developing Country Experience - Das-Gupta (Arindam); Mookherjee (Dilip) (2000)
Incentives ; Institutional Reform ; Tax Enforcement
22.5
Keywords: Incentives ; Institutional Reform ; Tax Enforcement